1974
DOI: 10.1172/jci107543
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Derivation of Transcobalamin III from Granulocytes ENHANCEMENT BY LITHIUM AND ELIMINATION BY FLUORIDE OF IN VITRO INCREMENTS IN VITAMIN B12-BINDING CAPACITY

Abstract: A B S T R Anormal granulocytes, appear to contain mainly TC III.No TC II was present in any of the sonicates. The general practice in most laboratories has been to determine serum UBBC. Because in vitro increments of up to 119% were found to occur in serum, this practice should be replaced by collection using methods that prevent such increments. Blood collected in EDTA-47 mM NaF had a stable, reproducible UBBC with no significant in vitro increment with time.EDTA-NaF UBBC was 640±168 (range 380-921 pg Bra bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This lack of selectivity appears to enhance the antibacterial function of GRP since this protein can bind Cbl and Cbl analogues and make them unavailable for certain bacteria that require them for growth. GRP has the following characteristics that favor it over TC II in terms of competing for binding of Cbl analogues in vivo: (a) GRP has a higher affinity for Cbl and Cbl analogues than TC II; (b) GRP retains its high affinity over a pH range of [2][3][4][5][6][7][8][9][10][11][12] whereas that of TC II decreases markedly below pH 5 (39) and is thus relatively ineffective in areas of necrosis or infection; and (c) GRP is located in the specific granules of granulocytes (40) from which it is released into phagosomes and also extracellularly (41,42). The enhanced ability of GRP to bind Cbl analogues enables them to be transported exclusively to hepatocytes rather than to other tissues which may be more susceptable to their toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…This lack of selectivity appears to enhance the antibacterial function of GRP since this protein can bind Cbl and Cbl analogues and make them unavailable for certain bacteria that require them for growth. GRP has the following characteristics that favor it over TC II in terms of competing for binding of Cbl analogues in vivo: (a) GRP has a higher affinity for Cbl and Cbl analogues than TC II; (b) GRP retains its high affinity over a pH range of [2][3][4][5][6][7][8][9][10][11][12] whereas that of TC II decreases markedly below pH 5 (39) and is thus relatively ineffective in areas of necrosis or infection; and (c) GRP is located in the specific granules of granulocytes (40) from which it is released into phagosomes and also extracellularly (41,42). The enhanced ability of GRP to bind Cbl analogues enables them to be transported exclusively to hepatocytes rather than to other tissues which may be more susceptable to their toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Transcobalamin III binds weakly to DEAE, has 1-mobility on serum electrophoresis, is essentially unsaturated with Br2, and appears to be released in large part from granulocytes in vitro after blood is collected (20). Transcobalamin I binds tightly to DEAE, has a-mobility on serum electrophoresis, is 70-100% saturated with B12, and does not appear to be released from granulocytes in vitro in significant amounts (21). Recent studies (22) have demonstrated that normal plasma transcobalamin I contains more sialic acid and less fucose than transcobalamin III and that transcobalamin I has a carbohydrate composition that is essentially identical to those of the two hepatoma Ba2 BPs.…”
Section: Discussionmentioning
confidence: 99%
“…Manual methods to determine UBBC are available 17. The reference range for UBBC is 670–1200 ng/L;18 for plasma collected into EDTA-sodium fluoride, it is 505–1208 ng/L;19 for haptocorrin, 49–132 ng/L; and for transcobalamin, 402–930 ng/L.…”
Section: Serum B12 Assaysmentioning
confidence: 99%